New and poorly known species of Bairdoppilata and Paranesidea (Bairdiidae, Ostracoda) from French Frigate Shoals and O’ahu, the Hawaiian Islands - Maddocks, Rosalie F. (Zootaxa, 2015)
Bairdoppilata scaura, n. sp. and five species of Bairdoppilata and Paranesidea in open nomenclature are described from encrusting communities on French Frigate Shoals and Kane’ohe Bay, Oahu, Hawaiian Islands. Some poorly documented anatomical traits (carapace setae, hingement, antennal claws, genitalia) are examined for their potential taxonomic significance, in order to confirm the coherence of the Genus Bairdoppilata and to explore its diversity.